The Study of Being in Plato and Aristotle - Nathan, Aidan R. (Peitho. Examina Antiqua, 2023)
Usage of the Greek verb ‘to be’ is generally divided into three broad categories — the predicative use, the existential and the veridical—and these usages often inform the way we understand Being in ancient philosophy. This article challenges this approach by arguing that Being is not the product of linguistic reflection in Parmenides, Plato and Aristotle; rather, these thinkers treat Being as the ontological and epistemological primary. Though this may overlap with the linguistic senses, it is not the same thing. The article is divided into three sections: the first one raises several basic issues with the predicative interpretation of Being, the second argues that Being is unified and singular in a significant sense and the third brings out the special pre-immanence of Being.